Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnagi.2021.605900
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Integrity of Corpus Callosum White Matter Hyperintensity Penumbra Predicts Cognitive Decline in Patients With Subcortical Vascular Mild Cognitive Impairment

Abstract: Loss of white matter (WM) integrity contributes to subcortical vascular mild cognitive impairment (svMCI). Diffusion tensor imaging (DTI) has revealed damage beyond the area of WM hyperintensity (WMH) including in normal-appearing WM (NAWM); however, the functional significance of this observation is unclear. To answer this question, in this study we investigated the relationship between microstructural changes in the WMH penumbra (WMH-P) and cognitive function in patients with svMCI by regional tract-based an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Therefore, pathological changes often occur in the corpus callosum, even when ischemia or hypoxia is mild. Previous studies reported that the strongest associations between abnormal DTI parameters and cognitive decline were in the corpus callosum and corona radiata ( 14 , 37 41 ). In our study, we also found that abnormalities of the corpus callosum and DKI parameters were strongly represented.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, pathological changes often occur in the corpus callosum, even when ischemia or hypoxia is mild. Previous studies reported that the strongest associations between abnormal DTI parameters and cognitive decline were in the corpus callosum and corona radiata ( 14 , 37 41 ). In our study, we also found that abnormalities of the corpus callosum and DKI parameters were strongly represented.…”
Section: Discussionmentioning
confidence: 96%
“…Our study found that hypertension scores and MoCA scores show a significant correlation with decreased connectivity in corpus callosum and ILF. Previous studies have reported that disruption of the corpus callosum microstructure especially the WMHL penumbra of the corpus callosum body may contribute to cognitive deficits associated with subcortical ischemic vascular disease (Qiu et al, 2021). Microstructural disruption of the right IFOF and ILF contributes to WMHL-related cognitive impairment (Chen et al, 2020) which is basically consistent with our research results, the effect of WMHL on the microstructural integrity of WM tracts may propagate along tracts to distal regions beyond the penumbra (Liu et al, 2021), In addition, in our study, decreased connectivity in left thalamoparietal pathways and left cerebellar were negatively correlated with MoCA scores.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the frontal–subcortical network can occur in the form of white matter lesions or microbleeds affecting pathways that connect cortical and subcortical regions, which result in cognitive impairments in executive function and attention (Ye and Bai, 2018 ). It is widely thought that white matter tracts in the CC harbor commissural fibers connecting the frontal lobe (FL) and other cortical areas, which can be damaged at the early stage of CSVD (Qiu et al, 2021 ). Overwhelming evidence indicates that brain network disorders lead to cognitive impairment of CSVD, and damaged network structure accounts for the association between CSVD neuroimaging lesions and cognitive deficits (Vasquez and Zakzanis, 2015 ).…”
Section: Discussionmentioning
confidence: 99%